Analysis of Factors Influencing Compliance with the Implementation of Surgical Safety Checklist - Daryani Daryani; Sri Sat Titi Hamranani; Very Wijaya (GLOBAL HEALTH SCIENCE GROUP, 2023)
The use of a checklist will be very effective if it is supported by the compliance of medical personnel in implementing it. Objective: to determine the factors that influence adherence to the implementation of the surgical safety checklist in IBS RSUP dr. Soeradji Tirtonegoro Klaten. Methods: This study used a survey method with a cross-sectional approach. The sampling technique used total sampling, as many as 57 nurses. The data collection instrument uses a questionnaire that has been tested for validity and reliability. Statistical test using person correlation, chi square and multiple logistic regression analysis. Results: Bivariate test between age and compliance (p= 0.914), gender and compliance (p= 0.114), education and compliance (p= 0.037), years of service and compliance (p= 0.718), knowledge and compliance (p= 0.002) and motivation with obedience (p = 0.421). Multivariate test of education (p= 0.013; OR= 0.433) and knowledge (p= 0.010; OR 0.210). Conclusion: Factors related to adherence to the implementation of the surgical safety checklist at IBS RSUP dr. Soeradji Tirtonegoro Klaten is education and knowledge. The most dominant factor affecting adherence to the implementation of the surgical safety checklist at IBS RSUP dr. Soeradji Tirtonegoro Klaten is education.